Burden in primary informal caregivers of children and adolescents with type 1 diabetes: Is it associated with depression, family dysfunction, and glycemic control? - Balcázar-Hernández, Lourdes; Huerta-Martínez, Hebert; Garrido Magaña, Eulalia; Nishimura-Meguro, Elisa; Jiménez Márquez, Abigail; Rivera-Hernández, Aleida (Frontiers in Endocrinology, 2023)
Objective. The requirement of a chronic treatment and the increase in life expectancy in children with type 1 diabetes (T1D) leads to the possibility of caregiver burden. The aim of our study was to evaluate the burden in primary informal caregivers (PIC) of children and adolescents with type 1, and its association with depression, family dysfunction and glycemic control. Materials and methods. A retrospective study was performed in PIC of children and adolescents with T1D. Zarit Burden Interview Scale (ZBIS) was used to evaluated caregiver burden. Beck Depression Inventory (BDI–II) was used to evaluated depression in PIC, and the Family APGAR questionnaire was used to evaluate the family functionality. Results: A total of 100 PIC of children and adolescents with T1D were included. Caregiver burden was found in 33% of caregivers. The total score of Zarit scale was 41 (34-49); 19 % had mild caregiver burden and 14% had severe caregiver burden. According to the BDI–II, the 82 % had minimal depression, 11% mild depression, 5% moderate depression and 2% severe depression. Family function was good in 69%; 13% had moderate dysfunction and 18% had severe dysfunction. A positive correlation between caregiver burden and BDI-II score (r=0.84; p=0.001) and the grade of depression (r=0.87; p=0.001) was found. A logistic regression model showed that BDI-II score was associated with caregiver burden (OR 1.14; 95%CI 1.061-1.23; p= 0.001). A BDI-II cut off of 9 or more had a sensibility and specificity of 58 and 28%, respectively, for caregiver burden [AUC 0.751 (0.64-0.85); p=0.001]. The BDI–II score  9 was a predictor of caregiver burden (OR 3.4; 95% CI 1.4-8.1; p=0.008) Conclusion. The caregiver burden is present in more than one third of the PIC of patients with T1D and is associated with depression. A BDI–II score  9 is a predictor of caregiver burden which may be a point to take into account in the integral approach to the patient with T1D and his or her family nucleus.